Ironia i komizm we współczesnej słowiańskiej antyutopii literackiej (na przykładzie powieści E. Bondy’ego, T. Konwickiego, W. Wojnowicza, W. Pielewina) - Bakuła, Bogusław (Slavia Occidentalis, 2011)
The article focuses on the problem of irony and comicality in the modern literary Slavic antiutopia. The analysis has been made on the example of the following novels: Egon Bondy’s Invalidní sourozenci, Tadeusz Konwicki’s Small Apocalypse, Vladimir Voynovich’s Moscow 2042 and Victor Pelevin’s Chapayev and Blankness. Irony and comicality in modern and postmodern literary antiutopia is transformed into intertextual or metaphysical grotesque.